Application of Cross-correlation Analysis Method for Measurement of the Fluid Flow Rate Based on X-ray Radiation; Journal of Nano- and Electronic Physics; Vol. 11, № 1 - Borodulya N. A. Nikolay; Rezaev R. O. Roman Olegovich; Chistyakov S. G. Sergey Gennadevich; Smirnova E. I. Ekaterina Ivanovna; Gogolev A. S. Aleksey Sergeevich; Filatov N. A. Nikolay Alexandrovich (2019, 2019)
Title screen